ANALISIS KINERJA STEWARD DALAM PROSES MAINTANANCE EQUIPMENT PADA FOOD AND BEVERAGE SERVICE YUAN GARDEN HOTEL JAKARTA - Sangari, Fonny; Lumare, Mercy A; Tuwaidan, Altje Ellen; Sambeka, Vesty Like; Tenda, Mirjam Pratidina (HOSPITALITI DAN PARIWISATA, 2025)
This study aims to analyze the role of stewards in the equipment maintenance process at Food and Beverage Service Yuan Garden Hotel Pasar Baru. Chinaware, glassware, and silverware equipment are essential equipment in Food and Beverage Service operations, used by guests when eating and drinking at restaurants or ordering room service. However, continuous use can leave spots or change the color of equipment if not noticed. Therefore, the maintenance process carried out by stewards is very important to prevent guest complaints. The research method used was a qualitative description involving all steward staff in the Food and Beverage Service department of Yuan Garden Hotel as the research population and the data collectionmethods used were interviews, observations, and documentation. The results showed that the role of stewards has a significant influence on Food and Beverage Service operations, especially in the process of chinaware equipment maintenance. The conclusion of this study is that the role of stewards is very important in the smooth operation of Yuan Garden Hotel's Food and Beverage Service. And with the addition of Human Resources in the steward division, it is expected to help operations so that they run well